Enacting Positive Social Change: A Civic Wealth Creation Stakeholder Engagement Framework. (January 2023) - Bailey, Ryan C.; Lumpkin, G. T.
Entrepreneurship is an innovative solution for many businesses, communities, governments, nonprofits, and social innovators to address societal issues, such as poverty and social injustice. Civic wealth creation (CWC) is one type of entrepreneurial change process that engages diverse stakeholders to enact positive social change (PSC). However, resistance to change and low stakeholder engagement often impede efforts to achieve desired outcomes. Because stakeholder theory holds that stakeholders with joint interests create new value when they interact, we propose a stakeholder engagement framework that uses the awareness, desire, knowledge, ability, and reinforcement (ADKAR) change methodology to enhance CWC stakeholders' propensity to participate in the entrepreneurial change processes that create PSC.